How do parents and school staff conceptualize parental engagement? A primary school case study - Jones, Cat; Palikara, Olympia (Frontiers in Education, 2023)
Understanding what different stakeholders mean by “parental engagement” is vital as school leaders and policy makers increasingly turn to parental engagement to improve pupils’ outcomes. Yet, to-date, there has been little examination of whether parents’, teachers’, and school leaders’ conceptions of parental engagement match those used in research and policy. This case study used online questionnaires to explore the conceptions of parental engagement held by 103 parents and 40 members of staff at one large English primary school. The results showed that only a quarter of school staff conceptualized parental engagement in relation to learning at home and that school leaders appeared to overestimate the impact of school-based activities. This is at odds with previous research suggesting that it is parental engagement with learning in the home – rather than parents’ involvement with school - that is associated with pupil attainment. This suggests that there might be a striking mismatch in the way that parental engagement is conceptualized by researchers advocating for its efficacy, and by school staff devising and implementing parental engagement initiatives. It is vital to raise awareness of this possibility amongst practitioners, researchers, and policy makers because any such mismatch could result in the misdirection of time and resources and the undermining of parental engagement’s potential as a powerful tool for raising attainment and closing achievement gaps.